ANALISIS EFISIENSI DAN KESELAMATAN SAAT BERKENDARA DENGAN SEPEDA MOTOR MENGGUNAKAN MATERIAL BAN HARD COMPOUND - fakhruddin khairan (IKIP PGRI KALIMANTAN TIMUR, 2026)
Motorcycle tire material plays a crucial role in determining riding efficiency and safety. This study aims to compare soft-compound and hard-compound tires in terms of usage efficiency and safety aspects. The methodology involved performance testing under various road and weather conditions, measuring parameters such as grip, vehicle stability, wear rate, and fuel consumption. The results indicate that soft-compound tires significantly enhance riding safety, particularly regarding grip on both dry and wet roads, as well as during cornering maneuvers and emergency braking. However, soft-compound tires exhibit a higher wear rate than hard-compound tires, resulting in a shorter lifespan and potentially higher long-term operating costs. The choice between soft-compound and hard-compound tires should take into account the rider's priorities specifically, whether they value optimal safety or long-term efficiency. This study is intended to serve as a reference for riders in selecting tires that best suit their needs and riding characteristics